Micro-daily events at work: Do they really matter for well-being? - Junça Silva, A.; Caetano, António; Lopes, M. (Well-being in contemporary society: international conference on the philosophy and science of well-being and their practical importance, 2012)
In everyday life people have different emotional reactions (both pleasant and unpleasant) to events. As positive and negative micro-events occur in our daily lives we frequently shift perceptions of how well we are doing accordingly (Heller, & Watson, 2005). Sometimes these events are insignificant and have little or no influence on our broader perceptions of life. Occasionally, however, they are life-changing events that have deep implications for an individual’s well-being. Together with these unforeseen occurrences are anticipated events, both within and beyond the workplace that shape the underlying structure of our daily lives (Stone, 1987). These micro-events are experienced and evaluated as daily hassles and uplifts, and seem to influence the individual’s perceptions of well-being as well as their performance. Despite their daily frequency at work, there is insufficient evidence to systematize what the main micro-events are, or to draw specific conclusions about their effect on an individual’s welfare and performance. For instance, Pekrun and Frese (1992) noted that there was very little research that focused on daily events at work and about their effects. Though there are numerous empirical demonstrations of events influencing well-being, most of these involve general life events and stressful events regarding their physical and mental consequences (Fay, & Sonnentag, 2010). Empirical studies concerning the influence of daily-events at work on well-being are scarce (Ilies, et al, 2011). Additionally, most studies resort to methods that do not allow the exploration of how those daily situational factors influence employee effort, performance and productivity (Ilies, Wilson, & Wagner, 2009). Moreover, the role of management practices, particularly those relating to human resources, regarding the relationship between micro-daily events and employee performance remains largely unexplored. Recently, organizational researchers have embraced these issues, as evidenced by a number of studies adopting diverse forms of diary methods (e.g. day reconstruction method: Kahneman, & Krueger, 2006; experience sampling methodology: Stone & Shiffman, 1994) to capture fluctuations in well-being at work over time (e.g. Weiss, Nicholas, & Daus, 1999). For instance, research on subjective well-being has revealed the existence of diverse work related micro-events that occur frequently throughout the working day and thus have a significant effect on individuals’ well-being and productivity (Nezlek, 2007). Affective events theory (AET: Weiss & Cropanzano, 1996) is one relevant theory within this perspective because it has explored the fleeting nature of emotional reactions, and their effects in the workplace. This theory assumes that several events at work (positive or negative) have immediate affective consequences that give rise to emotional reactions, and consequently emotional fluctuations (Walter & Bruch, 2009). These momentary emotions influence employee´s work related behaviours and attitudes. Furthermore, cognitive evaluation theory is also relevant since this theory assumes that micro-events stimulate emotional reactions, but these are mediated by an individual’s interpretation and evaluation of the event (Lazarus, 1999). These evaluations influence employee’s subsequent decisions regarding work and organization, such as turnover intentions, absenteeism, and extra-role behaviors (Ilies, Keeney, & Scott, 2011). Clearly, management practices, work environment and job characteristics promote conditions for the occurrence of different types of events that influence work related attitudes and behaviours (Fisher & Noble, 2004). Encouraged by the importance of daily-events at work and the implications for employees and the organization itself and with the aim of contributing to the further development of this issue, this exploratory study aims to identify the main micro-daily events at work with regard to levels of individual productivity and well-being. To achieve our goals we collected the data through semi-structured interviews. The design and format of these interviews schedule was adapted from questionnaires used previously in research on emotions in the workplace (Fitness, 2000; Basch, & Fisher, 1998). First, respondents were asked to answer the Scale of Positive and Negative Experiences (Diener, et al, 2010). This scale is composed of twelve items; six items relate to positive experiences and the other six concern negative experiences. For both positive and negative items, three are general (e.g., positive, negative) and three are more specific (e.g., joyful, sad). The scale is based on the amount of time the participant experienced each feeling over the previous week. Each item is scored based on how often they experienced those feelings, and ranged from 1 (very rarely or never) to 5 (very often or always). Then and according to the emotions identified on the scale as most frequent, they were asked to remember the events that aroused the emotions, and to describe what had happened. Participants were then asked to answer a detailed series of open-ended questions about the event, including the status of the persons involved, the nature of the event that had stimulated their emotion, what they were thinking and feeling at the time, how they had behaved, both at the time and later, and whether or not they considered the incident had been successfully resolved. After answering the open-ended questions, respondents also rated their recalled intensity of the emotion in response to the event, how long the effect of the emotion lasted, and the importance of the event. All the answers were given on a 7-point Likert scale. All the participants were gathered by the snowball method. They were full-time employees aged between 32 and 58 years old. 73% of the participants were female. Organizational tenure was 24 years on average (SD=9.87). The overall purpose of the study was explained to the participants in advance, and the importance of following the interview schedule and obtaining accurate, detailed data was stressed. Signed consent forms for participants´ interviews were given to them in order to assure that their responses were confidential and anonymous. The interview data were coded in two steps. In the first one, free responses for every question category (e.g. types of events; emotional experiences, event-related behaviors) were transcribed in full. After that, two independent raters sorted these responses into categories, according to their thematic similarity. . For instance, regarding the question to describe the event (“type of event”), a description of taking breaks throughout the working day, telling jokes with colleagues, or going for coffee were categorized as examples of “pleasant/agreeable breaks/interruptions”. Whereas descriptions related to being interrupted by the phone, or receiving lots of e-mails (that are not urgent or priorities) and that require an answer were categorized as examples of “unpleasant/disagreeable breaks/interruptions”. Similarly, in relation to “event-related behaviors” telling others what has happened, looking for help, or coping were categorized as examples of “social sharing”, while keeping quiet, walking away, or ignoring the situation were categorized as examples of “immediate withdrawal”. The aim was to develop a succinct but informative coding system that would capture the range of responses as economically as possible without being either under or over inclusive. In the second step of the coding, the two independent raters compared the set of categories sorted and classified by them. Both raters agreed on 85% of the cases and the other cases were then discussed to achieve consensus between both raters. After coding all the responses, five categories of positive job-related micro-events emerged: goal achievement, interpersonal pleasant relationships, favorable working conditions, pleasant breaks and receiving recognition. Likewise, nine categories of negative work-related micro-events emerged: unfavorable working conditions, lack of goal achievement, immoral behavior, interpersonal unpleasant relationships, others’ mistakes/incompetence, public humiliation, perceived disrespect/arrogance, unpleasant breaks and not receiving recognition. The five positive work-related events that emerged are briefly described below. Receiving recognition refers to positive feedback from managers, supervisors and/or work colleagues for meeting targets, performing a job to a high standard, or receiving a "pat on the back" for good performance or helpful behavior. Interpersonal pleasant relationships refer to agreeable situations or behaviors towards oneself or towards others by work colleagues, managers, and supervisors. Pleasant breaks are events described as voluntary and enjoyable work interruptions such as, going for a coffee, interacting with other co-workers in a satisfying manner. Goal achievement describes situations where job related targets, or goals were met. Favorable working conditions refer to events that seem to facilitate and enhance the individuals´ work performance (e.g., space, illumination, software). The nine categories of negative work-related micro-events are briefly described. Lack of recognition describes events where meeting targets, performing a job to a high standard, or engaging in helpful behavior, are ignored by supervisors and managers. Interpersonal unpleasant relationships refer to disagreeable behaviors or situations towards oneself or others by work colleagues, managers, supervisors and/or customers. Unpleasant breaks identify unwanted interruptions of the work, for instance, interruptions by phone calls, by non-urgent e-mails or by redundant questions. Lack of goal achievement involves situations where job related targets or goals were not achieved. Unfavorable working conditions refer to physical conditions and situations that seem too difficult and decrease the individual’s performance. Immoral behavior illustrates situations in which the respondent perceived that a colleague had behaved in a morally reprehensible way, such as being lazy or dishonest; telling lies, stealing, cheating (e.g. on expenses), `bullying' or taking advantage of others, or conducting a sexual relationship with a supervisor or subordinate. Others’ mistakes/incompetence describes events that hampered the respondent's ability to get the job done, or that cost the company money or goodwill; mistakes that may have been unintentional, but that nevertheless resulted in unintended yet detrimental consequences. Public humiliation involved incidents where the respondent had been directly and publicly humiliated by the offender (e.g., sexual harassment, or public criticism), in particular in front of customers or colleagues. Perceived disrespect/arrogance involves perceptions that an offender was acting in an arrogant or disrespectful manner. Results of the present study show the existence of several positive and negative micro-daily events at work that give rise to emotional reactions. Participants reported 29 positive and 29 negative events or situations. The average number of responses per person was 5, with a range from 2 to 7. The results of the present study show that the most frequent overall positive event category was “interpersonal pleasant relationships”, while the most frequent overall negative category was “others’ mistakes/incompetence”. In relation to emotional reactions, data showed that the most frequent positive emotion identified by the participants was joy and the most frequent negative emotion was displeasure (19 per cent). The purpose of this exploratory study was to identify the main micro-daily events at work. As expected, the data evidenced that positive daily events (e.g. interpersonal pleasant relationships) are associated to positive emotional responses (e.g. contentment) as well as negative daily events (e.g. unpleasant breaks) arouse negative emotional reactions (e.g. irritation). In addition, it seems that different daily events are related to different durations of emotional of reactions over the working day. Results also evidenced that some of these micro-events seem to be associated to different levels of subjective well-being and productivity. The results of this study might be useful to managers who wish to improve the emotional quality of life of their employees. Clearly, there is much to be gained, from knowing when and why employees experience positive and negative events that might affect their daily performance and well-being.